Sitting Alone with a Text. Issue 1 (15th September 2020) - Lohr, Joel N.
Abstract : This essay explores how frameworks of education in the United States have been shaped by particularly Protestant ideals—and, especially, how notions concerning individuals and their engagement with texts have had an outsized influence on educational practice. Following an examination of a number of historical issues related to our topic, and in particular Protestantism and the rise of the printing press, I examine the foundations of American education, including Puritan models of schooling as religious instruction. This leads to a discussion of the birth of Pluralism and Fundamentalism in the United States, which in turn leads to some reflections on the current educational milieu in this context, especially as related to religious identity in the classroom and higher education more generally. I suggest that a greater awareness of the cultural values that are embedded in our educational practices is vital if we are going to be responsive to the needs of increasingly diverse student populations.